Water quality monitoring system for aquaponics and fishpond using Wireless Sensor Network - Mohd Pu'ad, Muhamad Farhan; Sidek, Khairul Azami; Mel, Maizirwan (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
The higher the human population, the higher the demand for food supply from the agriculture sector. However, healthy and environment-friendly plant-based food production is very time-consuming. Water quality checking by the human resource is no longer efficient in the presence of technology today. Thus, a water quality monitoring system for aquaponics and fishpond is proposed in this study adapting the use of Wireless Sensor Network (WSN), Message Queuing Telemetry Transport (MQTT) protocol, and Wi-Fi signal. The completed system was successfully tested and implemented at the Malaysian Institute of Sustainable Agriculture (MISA). The devices send measurements to a base station which hosted a web server which can be viewed both locally and via the Internet. Results show the system is practical in use as it is both stable and reliable with 5 seconds maximum measurement refresh rate on its dashboard. Thus, reduces human dependency for monitoring the water quality of both the aquaponics and fishpond. Human resource can then be allocated to more crucial roles. Room for improvement includes complete use of solar renewable energy, adding Wi-Fi extender for large scale implementation, and equipping the Raspberry Pi with a cooling fan. This is the step forward to modernising agriculture.